2009
DOI: 10.1021/ie9005645
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Silver Nanoparticles Using a Spinning Disk Reactor in a Continuous Mode

Abstract: A spinning disk reactor (SDR) operated in a continuous mode was adopted for producing silver nanoparticles, aiming at an increase in the production rate. Two protecting agents, i.e., poly(vinylpyrrolidone) (PVP) and hydroxypropylmethyl cellulose (HPMC), were tested, which have been proven to be effective in our previous work of recycle operation. Using PVP as protecting agent, the effects of the operating variables, including the rotation speed, the feeding rate, the dosage of protecting agent, and reactant co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
2
19
0
Order By: Relevance
“…Kinetic control was possible in the synthesis of macrocyclic resorcin[4]arenes and pyrogallo[4]arenes (Figure 2C). [20] Condensation using both the VFD, and non-VFD conditions produced the thermodynamically favored isomers, with the exception of the condensation of vanillin and pyrogallol.…”
Section: Organic Transformationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Kinetic control was possible in the synthesis of macrocyclic resorcin[4]arenes and pyrogallo[4]arenes (Figure 2C). [20] Condensation using both the VFD, and non-VFD conditions produced the thermodynamically favored isomers, with the exception of the condensation of vanillin and pyrogallol.…”
Section: Organic Transformationsmentioning
confidence: 99%
“…Two p -phosphonic acid calix[5]arene molecules held together by a seam of H-bonds disassemble under shear stress, with the capsule then binding carboplatin in building a capsule for chemotherapy medicine (Figure 3A). [22] More recently, ≈100 nm diameter self assembled vehicles based on O -alkyl calix[4]arenes as phospholipid mimics has been developed for drug delivery, with the uptake of carboplatin in the vehicles increasing from undetectable levels in a round bottom flask to 75% with VFD processing. These high-loaded vehicles have a 4.5-fold increase in carboplatin loading efficiency on ovarian cancer cells relative to non-vehicle delivered carboplatin.…”
Section: Materials Transformationsmentioning
confidence: 99%
See 2 more Smart Citations
“…SDR (short for spinning disk reactor), which includes spinning disks (also known as rotors) and stationary disks (also known as stators), is one of the process intensification technologies employing high gravity-centrifugal force fields caused by the rotation of rotors. Extensive studies using this technology have shown that process time, reactant inventories, and impurity levels can be reduced by up to 99% (Brechtelsbaueret al, 2001;Cafieroet al, 2002;Clifford et al, 2009). …”
Section: Introductionmentioning
confidence: 99%